2000
DOI: 10.1046/j.1365-201x.2000.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive and non‐nutritive blood flow: rest and exercise

Abstract: There is growing evidence to support the notion of two vascular routes within, or closely associated with skeletal muscle. One route is in intimate contact with muscle cells (hence is known as 'nutritive') and the other functions as a vascular shunt (and has had the interesting misnomer of 'non-nutritive'). Recent findings suggest that the 'non-nutritive' route may, in part, be those vessels in closely associated (interlacing?) connective tissue that nourishes attached fat cells, and may form the basis of 'mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 47 publications
6
65
0
Order By: Relevance
“…Unlike in cardiac papillary muscles, polarographic studies of superfused preparations produce data similar in magnitude to the myothermic data. It is possible that even higher values would be recorded at 37°C, but it is very likely that local blood flow in vivo is controlled to keep intracellular PO 2 levels in a range where metabolism is down-regulated [142]. Moreover, it seems highly likely that there are also species differences in skeletal resting metabolism.…”
Section: Comparison With Skeletal and Smooth Musclesmentioning
confidence: 99%
“…Unlike in cardiac papillary muscles, polarographic studies of superfused preparations produce data similar in magnitude to the myothermic data. It is possible that even higher values would be recorded at 37°C, but it is very likely that local blood flow in vivo is controlled to keep intracellular PO 2 levels in a range where metabolism is down-regulated [142]. Moreover, it seems highly likely that there are also species differences in skeletal resting metabolism.…”
Section: Comparison With Skeletal and Smooth Musclesmentioning
confidence: 99%
“…Barrett et al (19) have recently imaged the endothelial transport process and showed that fluorescently labeled insulin is rapidly taken up and con-centrated in endothelial cells, which suggests that transit to the interstitium may be rate limiting. However, Clark and colleagues have suggested that insulin mediates multiple hemodynamic changes in the vasculature before acting on skeletal muscle, which could also account for the delay in insulin action (20,21).…”
Section: Research Design and Methods-intramuscular Injections Of Salimentioning
confidence: 99%
“…However, the time courses of these changes remain to be determined. The time associated with insulin-mediated redirection of flow to skeletal muscle (21) or changes in capillary permeability may help account for sluggish glucose disposal. Thus, we cannot discount the contribution of insulin's hemodynamic changes in limiting insulin-mediated glucose uptake.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 99%
“…Arteriovenous shunts connect the two plexuses and have an important role in thermoregulation (Braverman, 2000;Walloe, 2016). Nutritive blood flow refers to the route in direct contact with target cells, while nonnutritive refers vascular shunts (Clark et al, 2000). In the skin, capillary perfusion is regulated by terminal arterioles that feed capillary units.…”
Section: The Skinmentioning
confidence: 99%